Immunohistological Study of Palpebral Lobe of the Lacrimal Gland in Severe Dry Eyes Secondary to Stevens–Johnson Syndrome. (3rd June 2021) - Singh, Swati; Ali, Mohammad Javed; Mittal, Vikas; Brabletz, Simone; Paulsen, Friedrich
ABSTRACT: Purpose: To detect the immunohistochemical changes in the main lacrimal glands of patients suffering from chronic ocular sequelae of Stevens–Johnson syndrome (SJS). Methods: Histological sections of biopsies from the lacrimal gland of three chronic SJS patients (mean age, 33 years; 2 males) with severe dry eye disease (Schirmer = 0 mm) were assessed using double immunofluorescence techniques. Changes in the expression of secretory proteins lactoferrin (Lf), lysozyme (Ly), aquaporin 5 (AQP5), S-100, and early apoptosis marker (Annexin V) were studied. Results: Different morphological expressions of secretory proteins were present in the three samples. One sample had maintained the immunoreactivity for Lf, Ly, S-100, similar to healthy controls. Two samples had significantly reduced immunoreactivity for anti-Lf, anti-Ly, and S-100, the weakest being in the sample with distorted lobular architecture and mild interlobular fibrosis. AQP5 had a distinct vesicular intracytoplasmic immunoreactivity suggesting defective trafficking and integration of the protein to the apical membrane. There was no S-100 immunostaining in the acinar or ductal epithelium, whereas interstitial nerve fibers scattered in the periacinar region showed reduced immunoreactivity for S-100. There was strong Annexin V immunoreactivity in the nuclei of epithelial cells in the majority of acinar and ductal epithelia of all the samples, with distorted nuclear morphology in one sample. Conclusion: Defective trafficking of AQP5 and variable expression of Ly, Lf, S-100 are the notable findings in the lacrimal glands of chronic SJS patients along with signs of early apoptosis. It suggests that the palpebral lobe of the lacrimal gland is involved in the pathological processes occurring in the conjunctiva of SJS patients.